Characteristics of Photon Beam and Preservation of Coherence in Fourth-Generation Light Sources - Bonghoon Oh; Jinjoo Ko; Jaeyu Lee; Gyeongsu Jang; Seunghwan Shin (Applied Sciences, 2021)
Fourth-generation storage rings (4GSRs) that exploit the multi-bend achromat lattice concept may be able to surpass the brightness and coherence that are attained using the present third-generation storage rings. This paper presents the characteristics of photon beams and an analysis of their coherence properties in Korea-4GSR to represent 4GSRs.